Agreement Between Diaphragm Ultrasound and Pulmonary Function Testing in the Evaluation of Diaphragm Function in Patients with ALS (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: amyotrophic lateral sclerosis; diaphragm ultrasound; pulmonary function testing